Educação sexual e autonomia: estudo de uma intervenção com alunos do ensino médio do interior do estado de São Paulo - Campos, Thaís Emília de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Sex Education theme is becoming increasingly present in society, not only by aspects related to health, but also, the training of persons engaged in pleasurable sexuality considering not only the procreation. From this perspective, this research describes an intervention on sexual education that took place in a High School, using participatory methodology and consequent of a partnership with the Department of Health and with a campus of a public university in a city in the state of São Paulo. Participated in this study: two University professors, 80 school teachers and 1,350 students, and among these, seven were trained to be multiplier agents among his colleagues and received scholarships for scientific initiation of the Conselho Nacional de Pesquisa (CNPQ). The following procedures were used: 1) Bibliographic survey; 2) In-loco observation; 3) Intervention, by using the following means: a)observation: logbook, questions box, the words and the enclosed questionnaire; b) intervention: the logbook. Answered the enclosed questionnaire 227 participants, as follows: 31 school teachers and 196 students. The data analysis demonstrated that 59.5% are sexually active; that the predominant age of first intercourse among multipliers is 15.50 years old, the student group is 14.24 years old and among teachers is 19.85 years old. The average of sexual intercourse is 4.7 per month among students, 2.0 among multipliers and 3.2 among professors. Concerning the use of condoms, the students made greater use at first intercourse than the other groups. In the questions that raise the level of knowledge about STD / HIV / AIDS / Hepatitis, teachers correctly answered the most questions; which does not occur in relation to the issues outlined by the students. A reflection on what would be an appropriate sexual conduct, considering the adolescent's autonomy, is rarely present in school spaces. When it occurs, involving many barriers and conflicts. So, I...

O tema Educação Sexual está cada vez mais presente na sociedade, não só pelos aspectos relacionados à saúde, mas também, pelo exercício de uma sexualidade prazerosa, não tendo em vista somente a procriação. Nesta perspectiva, esta pesquisa descreve uma intervenção sobre Educação Sexual que ocorreu em uma Escola de Ensino Médio, utilizando metodologia participativa e resultante de uma parceria com a Secretaria de Saúde e com uma unidade de uma Universidade Pública em uma cidade do interior do Estado de São Paulo. Foram participantes do estudo dois professores da Universidade, 80 professores da escola e 1350 alunos, sendo que entre estes, sete receberam formação para serem agentes multiplicadores entre seus colegas e receberam bolsas de iniciação científica do Conselho Nacional de Pesquisa (CNPQ). Foram utilizados os seguintes procedimentos: 1) levantamento bibliográfico; 2) observação no campo; 3) intervenção, utilizando-se dos seguintes instrumentos: a) Observação: diário de bordo; caixa de dúvidas, as palavras e o questionário fechado; b) intervenção: diário de bordo. Responderam ao questionário fechado 227 participantes, sendo: 31 professores do Ensino Médio da escola e 196 alunos do Ensino Médio. A análise dos dados quantitativos, evidenciou que 59,5% têm vida sexual ativa; que a idade predominante da primeira relação entre os multiplicadores é de 15,50 anos, no grupo dos alunos é de 14,24 anos e entre os professores é de 19,85 anos. A média de relações é de 4,7 ao mês entre alunos, de 2,0 entre multiplicadores e 3,2 entre professores. Em relação ao uso de preservativos nas relações sexuais, os alunos fizeram maior uso na primeira relação que os demais grupos. Nas questões que levantam o nível de conhecimento sobre DST/Aids, os professores responderam corretamente à maior parte das questões; o que não ocorre em relação às respostas...
Keywords: Ensino médio - São Paulo (Estado); Educação sexual; Autonomia (Psicologia); Education, Secondary